Towards ecological and social impact through collaborative governance of a seascape of marine protected areas in Honduras. Issue 4 (26th July 2021) - Steadman, Daniel
Abstract: Protecting marine biodiversity and ensuring sustainable use through a seascape approach is becoming increasingly widespread in response to the ecological, social and institutional challenges of scaling ocean management. A seascape approach means clustering spatial management measures (marine protected areas) based around the principles of ecological connectivity, and developing or enhancing collaborative governance networks of relevant stakeholders (managers, community groups, non-governmental organizations) based around the principles of social connectivity. As with other large-scale approaches to marine management, there is minimal evidence of long-term impact in seascapes. This study uses a theory-based, participatory impact evaluation to assess perceived changes attributed to the Atlántida seascape in Honduras (initiated in 2015), encompassing three well-established marine protected areas and the non-legally managed waters between them. Using an adapted most significant change method, 15 interviews with a representative subset of seascape stakeholders yielded 165 stories of change, the majority (88%) of which were positive. Enhanced social capital, associated with cross-sectoral collaboration, inter-site conflict resolution and shared learning, was the most consistently expressed thematic change (32% of stories). Although most stories were expressed as activity- or output-related changes, a small proportion (18%) were causally linked to broader outcomes or impact around increased fish and flagship species abundance as well as interconnected well-being benefits for people. Although minimal (and occasionally attributed to prior initiatives that were enhanced by the seascape approach), this impact evidence tentatively links seascapes to recent related research around the effectiveness of appropriately scaled, ecosystem-based and collaboratively governed marine management that balances strict protection with sustainable use.